Delites™ supplementation prevents metabolic syndrome onset and modulates gut microbiome in male Sprague Dawley rats fed on cholesterol- and fat-enriched diet: a randomized preclinical trial study - Leonardo, Juan; Hertanto, Robby; Surya, Reggie; Syahputra, Rony Abdi; Humayrah, Wardina; Sabrina, Nindy; Taslim, Nurpudji Astuti; Tallei, Trina Ekawati; Tjandrawinata, Raymond Rubianto; Nurkolis, Fahrul (Frontiers in Nutrition, 2025)
BackgroundMetabolic syndrome (MetS) is a global health concern, characterized by a combination of dyslipidemia, insulin resistance, obesity, and hypertension, significantly increasing the risk of type 2 diabetes mellitus (T2DM) and cardiovascular diseases. Gut microbiota plays a pivotal role in MetS pathophysiology, with dysbiosis exacerbating metabolic impairments. Delites™, a supplement inspired by Traditional Chinese Medicine, has shown potential in modulating gut microbiota and mitigating MetS.ObjectivesThis study aimed to evaluate the effects of Delites™ supplementation on metabolic health and gut microbiota composition in male Sprague Dawley rats fed a cholesterol- and fat-enriched diet (CFED).MethodsA randomized preclinical trial was conducted on 32 rats divided into four groups: control-normal, CFED, CFED+low-dose Delites™ (54 mg/kg), and CFED+high-dose Delites™ (108 mg/kg). Parameters including lipid profiles, enzymatic activity, molecular biomarkers, and gut microbiota composition were analyzed.ResultsDelites™ significantly improved lipid profiles, reduced inflammation (TNF-α), enhanced anti-inflammatory markers (IL-10), and increased energy metabolism regulator PGC-1α. Gut microbiota modulation showed increased beneficial genera (Bifidobacterium, Lactobacillus) and reduced pathogenic Proteus, improving microbial diversity.ConclusionDelites™ supplementation effectively mitigates MetS through metabolic and microbiota modulation. These findings highlight its potential for precision medicine approaches to combat metabolic disorders. Further research is needed to explore its long-term effects and translational relevance in humans.